Angioarchitecture of the epididymis in camel (Camelus dromedarius) - ANURADHA, ANURADHA; JAIN, R K (The Indian Journal of Animal Sciences, 2014)
There were 4 epididymal arteries in camel which emanated at different levels of vascular cone of the testicular artery. These vessels descended along with the latter in convoluted manner and were surrounded by pampiniform plexus. The epididymal artery 1 and 2 arose in succession from the apex of the vascular cone and supplied blood to head and proximal segment of the body of epididymis whereas epididymal arteries 3 and 4 arose from base of the vascular cone and formed anastomoses with each other and descended along the body of the epididymis. The head, body and tail of epididymis had their independent venous radicles. These venous radicles united and reunited to form the epididymal vein at the base of the pampiniform plexus and then joined the plexus at its apex. However in 1 animal there were 2 epididymal veins. One of them joined the pampiniform plexus at the level of proximal one-third while the other joined at the apex of the plexus.